2020
DOI: 10.1097/md.0000000000023311
|View full text |Cite
|
Sign up to set email alerts
|

Low-site versus traditional peritoneal dialysis catheterization

Abstract: Background: The objective of this study was to compare the complications of low-site peritoneal dialysis (PD) catheter placement and traditional open surgery in peritoneal dialysis catheter insertion. Methods: The following databases were searched from inception to September 6, 2019: PubMed, Embase, the Cochrane Library, China National Knowledge Infrastructure, and Wanfang. Eligible studies comparing low-site PD catheter placement and traditional open surgery in periton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…Moreover, in the same study, it was reported that short-segment peritoneal catheter placement in the pelvis did not cause bowel movements, and omental wrapping complications were observed less frequently. [ 7 ] Our results are consistent with these findings.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Moreover, in the same study, it was reported that short-segment peritoneal catheter placement in the pelvis did not cause bowel movements, and omental wrapping complications were observed less frequently. [ 7 ] Our results are consistent with these findings.…”
Section: Discussionsupporting
confidence: 93%
“…Laparoscopic lysis of the adhesions is recommended to reduce catheter dysfunction. [ 7 ] In adhesions that do not minimize peritoneal capacity and disrupt its integrity, adhesions can be released by passing a 5 mm ultrasonic shears through the pull-apart sheath/dilator without the need for an additional trocar, which will prevent the insertion of a suitable PD catheter in the Douglas pouch in the pelvic region. [ 8 ] The larger the number of compartments and the greater the area occupied, the greater is the surgical intervention required.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies have reported using the "very low site approach" to reduce the risk of catheter migration. With this approach, the catheter is inserted a few centimeters above the suprapubic margin, reducing the risk of catheter migration [13][14][15]. This approach requires an adaptative catheter cut extending from the insertion point at the peritoneum to the pelvic floor.…”
Section: Insert Positionmentioning
confidence: 99%